Helical water chain mediated proton conductivity in homochiral metal-organic frameworks with unprecedented zeolitic unh-topology - Sahoo, Subash Chandra; Kundu, Tanay; Banerjee, Rahul (Journal of the American Chemical Society, 2011)
Four new homochiral metal-organic framework (MOF) isomers, [Zn(l-L-Cl)(Cl)](H2O)(2) (1), [Zn(l-L-Br)(Br)]-(H2O)(2) (2), [Zn(d-L-Cl)(Cl)(H2O)(2) (3), and [Zn(d-L-Br)-(Br)] (H2O)(2) (4) [L = 3-methyl-2-(pyridin-4-ylmethylamino)-butanoic acid], have been synthesized by using a derivative of L-/D-valine and Zn(CH3COO)(2)center dot 2H(2)O. A three-periodic lattice with a parallel ID helical channel was formed along the crystallographic c-axis. Molecular rearrangement results in an unprecedented zeolitic unh-toparigy in 1-4. In each case, two lattice water molecules (one H-bonded. to halogen atoms) form a secondary helical continuous water chain inside the molecular helix. MOFs 1 and 2 shows different water adsorption properties and hence different water affinity. The arrangement of water molecules inside the channel Was monitored by variable temperature single crystal X-ray diffraction, which indicated that MOF 1 has a higher water holding capacity than MOF 2. In MOF 1, water escapes. at 80 degrees C, while in T the same happens at a much lower temperature (similar to 40 degrees C). All the MOFs reported here shows reversible crystallization by readily reabsorbing moisture. In MOFs 1 and 2, the frameworks are stable after solvent removal, which is confirmed by a single-crystal to single crystal transformation. MOFs 1 and 3 show high proton conductivity of 4.45 x 10(-5) and 4.42 x 10(-5) S cm(-1), respectively, while 2 and 4 shows zero proton conductivity. The above result is attributed to the fact that MOF 1 has a higher water holding capacity than MOF 2.